The Basel III Financial Architecture and Emerging Regulatory Developments in Macro Prudential Tools - World Bank (Washington, DC, 2013)
This note reviews the main elements of the New Basel III global regulatory framework and its regulatory implications, as well as the menu of macro prudential regulatory options to consider for application to ensure more resilient banks and baking systems.